Sensitivity and Specificity Tests of Hemoglobin Examination Between Hemoglobinometer and Hematology Analyzer on Pregnant Mothers - Nurul Widowaty Arbie; Rita Amini Warastuti; Adnan Malaha (Journal of Health, Technology and Science (JHTS), 2020)
This study aimed to determine the sensitivity and specificity test of hemoglobin examination on pregnant women using Hemoglobinometer and Hematology Analyzer devices. The research method used a quantitative approach with the type of research being analytic observational research. The type of data used was primary data in the form of research results and secondary data in the form of data obtained from literature, books and documents. The sampling technique in this study was a purposive sampling technique, with a total sample of 73 people taken from the Kota Utara Public Health Center and Toto Kabila Regional General Hospital. The results showed that the hemoglobinometer has a sensitivity of 81% and a specificity of 100%, while the hematology analyzer has a sensitivity of 98% and a specificity of 100%.